Comparison of conformation trait scores of foals and adults in Posavje horse breed - Mesarič, Matjaž; Potočnik, Klemen (Anali PAZU, 2022)
The objective of the study was to detect the differences of the conformation scores between foals and adult Posavje horse breed. At the Department for selection of horses in Veterinary Faculty, data of conformation scores determines criteria for quality of breeding animals in breeding objective and registering in Studbook. Evaluating data of type, head, neck, front part, middle part, hind part, conformation of front limbs and hind limbs from 1995 till 2007 were analysed. Estimated heritabilities for scored conformations trait in Posavje horse (556) were low to moderate (0.03-0.37). The data included conformation valuation of Posavje horse breed male (57) and female foals (353) and adult at admittance in studbook. An average in ten-point scale in the group of mare was 7.25±0.50 for type, 7.39±0.32 for head-neck, 7.57±0.19 for body and 6.44±0.21 points for limbs. An average of valuation points for the same animals as foal was 7.37±0.39 for type, 7.18±0.37 for head-neck, 7.54±0.35 for body and 6.59±0.31 for limbs. A significant differences between valuation of this two groups (p<0.01) was found for type, head-neck and limb conformation traits (paired t-test). Valuation of body was similar in foals and adult animals. The conformation scores of male Posavje horses were for the same conformations traits higher than for female animals. A significant difference (p<0.01) was found only for head-neck. The results show that the relationship between conformation traits of female Posavje horses was weak. In male Posavje horses, the relationship between conformation traits was more informative, most likely because of stringent criterions at evaluation of conformation in foals. Further research in genetic parameters of conformation in young horses, as well as foals, should strengthen breeding programs of Posavje horses and allow earlier selection of superior breeding animals.